Tracing issues of the deferred/differed contemporary Australian jewish identity: Bavati’s Dancing in the Dark and Brous’I am Max Lamm under the deconstructive lens - Rasha Saeed Abdullah Badurais; Nurul Farhana Low Abdullah; Mohamad Rashidi Mohd Pakri (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study attempts to deconstruct Bavati’s Dancing in the Dark (2010) and Brous’ I Am Max Lamm (2011) to discuss the contemporary social-psychological identity features portrayed within the overall ethno-religious Australian Jewish identity perspective in these texts. Highlighting the bidirectional relationship between the social-psychological identity perspective (Breakwell, 1986), at the narrower level, and the overall ethno-religious Australian Jewish identity aspect (Landau, 2015 and Elazar, 1995) reveal significant aspects of Jewish identity features in the selected novels which have not previously received scholarly attention. Derrida’s différance is the chief theoretical analytic perspective to be employed through the textual analysis which relies on the elicited traces - beyond binaries, rhetorical expressions, semantic and morphosyntactic tell-tale textual moments. In the two novels, the ethno-religious perspective is explicit, in that Ditty and Lamm are trying to prove their Jewish selves confronting their ethnic and religious burden. This is shown through close analysis of the novels. Ditty’s final dance in the light and Lamm’s laughter at the end do not indicate the striking of a balance in their social-psychological identities, but instead marks a case of Jews in the postmodern era; their identity constantly deferred in the in-between, carrying the thousands-of-years’ heritage yet simultaneously, struggling to be recognised for outstanding personal achievements.